Length-Weight Relationships and Relative Condition Factor of Spicara flexuosum (Rafinesque, 1810) Inhabiting the Black Sea and the Turkish Straits System - ŞALCIOĞLU, Aslı Şükriye; SÖNMEZ, Adem Yavuz (Marine Science and Technology Bulletin, 2022)
Length-weight relationships and condition factor of Spicara flexuosum collected from İstanbul, Rize, Çanakkale and Sinop-Kastamonu by using commercial gill nets and hand-line fishing methods were evaluated between 2013 and 2014 in this study. The overall length-weight equation (W=0.0236 L2.7334) indicated negative allometric growth from all sampling periods. Samples collected from Istanbul and Çanakkale exhibited positive allometric growth while S. flexuosum showed negative allometric growth in Rize and Sinop-Kastamonu in December 2013 and January 2014 respectively. The relative condition factor among regions varied from 0.99 to 1.08, indicating a state of wellbeing among all locations. This study provides the baseline data of length-weight relationships and condition factor analyses for S. flexuosum species from Turkish coastal waters for future management purposes for this species.
Keywords: Hidrobiyoloji; Growth parameters; Marmara Sea; Picarel; Positive allometric; Hydrobiology; 14. Life underwater